Experimental study on the frosting characteristics of round tube in confined circular flow path at low temperature. (5th May 2020) - Lai, Tianwei; Ding, Pei; Dong, Xiaojun; Zhang, Beile; Chen, Xiaozhuan; Hou, Yu
Highlights: Transient frosting of circular tube in confined space is experimentally studied at −60 °C. Periodic frosting and melting of frost processes are observed in certain conditions. Frost growth rate under different ambient parameters are investigated independently. Frost distribution, heat transfer rate and average density in confined circular flow path are evaluated. Abstract: Frosting in confined spaces usually takes places on the cold surfaces in heat exchangers and other equipment. In order to study the frosting characteristics on the surface of a round tube in a confined space, a test rig is developed capable of visualizing transient frosting. The periodic melting and refrosting phenomena are captured and analyzed with the wall surface temperature of −60 °C. The roles of humid air velocity, air temperature, relative humidity and cold surface temperature on frosting have been expounded independently. Along the air flow path, the frosting thickness, accumulation, heat transfer rate and average density are compared under different air velocities, air temperatures, clod surface temperature and relative humidity and the correlations are proposed from dimensionless parameters. The results show that obvious stepwise periodic frosting and frost-melting appear due to the thermal resistance and heat transfer between the frost and the humid air when the frosting entered the mature stage. At a higher tube temperature, air temperature and relative humidity, the frosting melting and undulations emerged more frequently and the frost accumulation, heat transfer rate and average density increased. The frost layer thickness is uneven along the air flow path, which possesses the highest value in the middle position of tube and the lowest near the air inlet.